A new trophic interaction between invasive weed, its biological control agent, and local insects: A case study of Chromolaena odorata (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Authors. 2019. A new trophic interaction between invasive weed, its biological control agent, and local insects: a case study of Chromolaena odorata. Biodiversitas 20: 1006-1011. Invasive species have been known to cause biotic homogenization. The presence of Chromolaena odorata, an alien invasive weed, in agricultural habitat has outcompeted many crop plants. The presence of alien invasive weed creates a new trophic interaction especially with local herbivores as well as other associate insects. This study was aimed to investigate a new trophic interaction that has been established between C. odorata, its introduced biological control agent, and local insects. The research was conducted in various land-use types in both of Arjuno and Bromo mountain landscape. In each landscape, we surveyed the population density of C. odorata and its biological control agent (a gall fly, Cecidochares connexa) as well as observed the diversity and abundance of other insects associated with C. odorata. Samples were taken along the transect lines at various altitudinal gradients, from 400 to 1100 m asl. In total, 124 species of insects were found associated with C. odorata which include herbivores, parasitoids, and predators. The difference of land-use types affected the population density of C. odorata but not its herbivores (i.e. C. connexa and aphids). A new association was found between the introduced insect, C. connexa and local parasitoids. The field survey also discovered new associations between the invasive weed with local herbivores such as aphids that are found with high abundance. The aphids were found to have a symbiosis interaction with ants such as Anoplolepis gracilipes (invasive species) and Dolichoderus thoracicus. In conclusion, the ecological consequence of the presence of invasive weed species is the shaping of a new trophic interaction with local insects, even with other invasive ant species. This interaction arguably is part of an ecological process that formed an equilibrium interaction which may cause either a negative or positive impact on C. odorata.
Keywords: Anoplolepis gracilipes; aphid; Arjuno mountain; Bromo mountain; Cecidochares connexa